ABC for people with HIV: responses to sexual behaviour recommendations among people receiving antiretroviral therapy in Jinja, Uganda - Allen, Caroline; Mbonye, Martin; Seeley, Janet; Birungi, Josephine; Wolff, Brent; Coutinh, Alex; Jaffar, Shabbar (Taylor & Francis, 2011)
People living with HIV who are taking antiretroviral therapy (ART) are increasingly involved in ‘positive prevention’ initiatives. These are generally oriented to promoting abstinence, ‘being faithful’ (partner reduction) and condom use (ABC). We conducted a longitudinal qualitative study with people living with HIV using ART, who were provided with adherence education and counselling support by a Ugandan non- governmental organisation, The AIDS Support Organisation (TASO). Forty people were selected sequentially as they started ART, stratified by sex, ART delivery mode (clinic- or home-based) and HIV progression stage (early or advanced) and interviewed at enrolment and at 3, 6, 18 and 30 months. At initiation of ART, participants agreed to follow TASO’s positive-living recommendations. Initially poor health prevented sexual activity. As health improved, participants prioritised resuming economic production and support for their children. With further improvements, sexual desire resurfaced and people in relationships cemented these via sex. The findings highlight the limitations of HIV prevention based on medical care/personal counselling. As ART leads to health improvements, social norms, economic needs and sexual desires increasingly influence sexual behaviour. Positive prevention interventions need to seek to modify normative and economi
Keywords: HIV/AIDS; Anti-retroviral therapy; Sexual behaviour; Uganda